STUDY ON THE SURFACE FUNCTIONALIZATION OF NANOSILICA FOR OIL ADSORPTION - Phương, Hoàng Thị; Hồng, Nguyễn Khánh Diệu (Vietnam Journal of Science and Technology, 2016)
This study covered functionalization of the nanosilica with an organo – silico compound. The functionalization was established at 350oC for 4 hours after totally impregnating polydimethylsiloxane onto the beginning nanosilica. The adsorption ability of the two kinds of material was also tested for illustrating the great potential of the functionalized nanosilica. Some techniques were required including FT-IR, TEM and TG-DTG for characterizing the nanosilica samples.